The functions of public art in post-apartheid South Africa - Pretorius, Annette Sophia (My University, 2007)
The aim of this research report is to explore the extent to which public art in postapartheid, democratic South Africa may contribute both to urban regeneration and nation building as well as the extent to which contemporary African monumental public art could reflect African heritage and traditions (Nettleton 2003:3). Another issue that is explored is the role of patronage in determining the function of public art in post-apartheid South Africa. Case studies in the form of two examples of post-apartheid public, namely the Freedom Park and the Constitution Hill projects art are used to explore the functions of public art in South Africa. In summary this research report therefore analyses: • The nature and function of public art-historical issues; • The practical issues affecting the production of public art in post-apartheid South Africa; • The socio-political factors that mitigate for or against the ability of public art to function effectively in the post-apartheid South African context; and • How these functions feed into the broader issues of making a contribution in a demographically complex, post-apartheid South Africa.
Student Number : 0419845J - MA research report - School of Arts - Faculty of Humanities
Keywords: public art; post-apartheid South Africa